Cutaneous leishmaniasis: Spatial distribution and environmental risk factors in the state of Pará, Brazilian Eastern Amazon - Veiga Gonçalves, Nelson; Miranda, Claudia do Socorro Carvalho; Costa, Rodrigo Junior Farias da; Guedes, Juan Andrade; Matsumura, Erica Silva de Souza; Costa, Simone Beverly Nascimento da; Noguchi, Selma Kazumi da Trindade; Guimarães, Luis Henrique Rocha; Coelho de Oliveira, Rafael Aleixo; Simone Alves Tavares, Lívia; da Cunha Menezes Palácios, Vera Regina; Xavier, Marília Brasil (The Journal of Infection in Developing Countries, 2019)
Introduction: Cutaneous leishmaniasis is an infectious disease transmitted by phlebotomine sandflies and is considered a great environmental and public health problem. Thus, this work presents initial results of the analyses about the relationship between the spatial distribution of this disease and its environmental risk factors in three municipalities, in the state of Pará, Brazil, from 2012 to 2016. Methodology: It was used data from the Ministry of Health, the National Institute for Space Research and the Brazilian Institute of Geography and Statistics. The statistical and spacial analysis of the variables were done using G-test goodness-of-fit, kernel interpolation technique and the Bivariate Global Moran Index (I). Results: The analyses showed that the most affected individuals were males, adults, low schooling, residents in rural areas and small farmers. The disease spatial distribution was not homogeneous in the municipalities and it was associated to different relationships between the land use and occupation and the notificated cases density, with direct spatial autocorrelation. Conclusions: The deforestation was the most significant risk factor linked to the cases occurrence in all the studied area. We emphasize the need of intensification of epidemiological and environmental surveillance actions in the studied areas.